Barium Removal from Produced Water Using RCC-Based Ceramic Adsorbent: Fixed-Bed Column Adsorption - Herawati, Netty; Nasir, Subriyer; Roni, Kiagus Ahmad; Karim, Muhammad Arif (Science and Technology Research Centre Universitas PGRI Semarang, 2025)
This study focuses on the removal of barium ions (Ba²⁺) from produced water, a common challenge in industrial wastewater treatment due to barium’s toxicity and scaling potential. To address this, the research introduces a novel ceramic composite adsorbent formulated from natural clay and residue catalytic cracking (RCC) spent catalyst, combining low cost, sustainability, and enhanced adsorption performance. The main objective is to evaluate the adsorption efficiency of this composite in a fixed-bed column system under varying operational conditions, while also modeling its dynamic behavior. Produced water with an initial barium concentration of 0.58 mg/L (pH 8.8) was fed in up-flow mode at flow rates of 6, 7, and 8 mL/min using a peristaltic pump. Effluent samples collected over 180 minutes were analyzed by UV- Vis. spectrophotometry. Results showed that lower flow rates increased contact time and improved adsorption efficiency, with breakthrough delayed to 210 minutes at 6 mL/min compared to 160 minutes at 8 mL/min. Breakthrough modeling indicated that the Thomas model best represented the data (R² ≥ 0.95), while the Yoon–Nelson model reliably predicted 50% breakthrough time. This work demonstrates that clay–RCC ceramic composites are effective, low-cost, and sustainable adsorbents.